First record of the millipede family Haplodesmidae (Diplopoda: Polydesmida) from Colombia: two new species of Inodesmus Cook, 1896 from the Northern Andes - Juan Romero-Rincon; Santiago Alvear; Daniela Martínez-Torres; Jairo Robles-Piñeros (European Journal of Taxonomy)
The millipede family Haplodesmidae is reported from Colombia for the first time, represented by Inodesmus mesibovi sp. nov. and Inodesmus miconiae sp. nov. Their presence in primary and secondary oak forests suggests their native origin in Colombia. This discovery represents the first record of the genus Inodesmus Cook, 1896 in South America, with potential implications of further records of the genus and family from the continent. We also present the first record of teratologies in haplodesmid millipedes.